Pentingnya Penganggaran dalam Mengelola Keuangan Perusahaan - Muammar Khaddafi; Zahidah Zahidah; Siti Razqia Nabila; Azhar Humam Martua Hasibuan; Apriani Apriani (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
Budgeting is a crucial element in managing a company’s finances, as it provides clear and structured direction for decision-making and resource allocation. With effective budgeting, a company can optimize the use of its funds, minimize the risk of bankruptcy, and improve overall financial performance. This article aims to discuss the importance of budgeting in financial management, highlighting its role, benefits, and the challenges associated with its implementation.